A step forward in 3D measurements in alpine skiing: a combination of an inertial suit and DGPS technology - Supej, M. (Science and Skiing IV, 2008)
INTRODUCTION: Camcorder-based 3D measurements are already a Standard procedure in the science of alpine skiing. Fixed cam to pan-tilt-zoom solutions are used. Joints and/or segments are detected with manual capturing, auto marker recognition, and lately, even image processing auto detection without markers. Unfortunately, none of these methods provides great accuracy, a long and wide measurement area, the quick preparation of measurements, and fast or immediate results at the same time. The GPS system and accelerometers have already been used in alpine skiing (Skalaud & Limpach, 2003). This paper introduces a new 3D measuring procedure based on the differential GPS system and an inertial suit that satisfies most needs.